On the instability of majority decision-making: testing the implications of the `chaos theorems' in a laboratory experiment - Jan Sauermann (Theory and Decision, 2020)
In light of the so-called `chaos theorems' from social choice theory, William Riker (W. H. Freeman and Company, San Francisco, 1982) argues that the indeterminacy of majority rule leads to voting cycles making democratic decisions arbitrary and meaningless. Moreover, when the core is empty, majority instability correlates with the level of conflict among actors. This study uses laboratory committee decision-making experiments to provide an empirical test of both aspects of Riker's argument. Committees make repeated majority decisions over 20 periods picking points from a two-dimensional policy space. The experiment manipulates committee members' preferences and thus varies the existence of a core and the level of conflict between group members. The experimental results contradict Riker's interpretation of the chaos theorems' implications. Thus, the core exhibits less attraction than generally assumed. Moreover, an empty core is not associated with increased majority rule instability. Instead, conflicting preferences lead to more instability irrespective of the existence of an equilibrium.
Keywords: 300; Committee decision-making; Laboratory experiment; Majority rule; Social choice